Business science: Overproduction, self-citations and Article processing charge (APC) - Pinto, Adilson Luiz; Shirshahi, Saeid; Varmazyar, Reza; González-Valiente, Carlos Luis (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Business science is a field that has been facing some challenges recently, especially when it comes to overproduction (hyperprolific), excessive self-citations, and charging for publications in open-access journals. To shed light on these issues, a recent study was conducted based on three cases. The first case focused on super-producing authors, where an advanced search strategy was used to identify the ten most productive authors in Brazil in the last five years. The study found that these authors published a paper on average every 2,68 days, a staggering rate. Interestingly, these authors had a direct relationship and published their articles in collaboration, always in the same journal. The papers all dealt with RIFM fragrance ingredient safety assessment, and while they were typical mass production, the citations were very low. The second case examined self-citations, where a research group published 15 papers in the last five years, with seven of them published in a journal that the group had purchased. The analysis found that two of the most representative authors in the research group obtained a significant number of self-citations. Finally, the study looked at the costs associated with publishing in open-access journals. The analysis found that some journals charge many publishing fees for accessing and indexing on platforms, which can be a significant barrier to disseminating research. Overall, these cases highlight the challenges faced by the science industry and the need for measures to ensure fair and transparent practices.